Letter - Rodríguez Vega, José; Pretel, Felipe
011-0018-001 Unión General de Trabajadores de España FUENCARRAL, 93 MADRID TELÉFONO 12139 Los sobres que se nos envien deberán redactarse asi: Unión General de Trabajadores CALLE DE LA PAZ, 44 SECRETARIA VALENCIA W.M. Citrine Transport House LONDON. Paris, November 20th 1937. Núm. Dear Comrade Citrine, Although we did our utmost to make with all the haste possible in the present circumstances the journey which we had announced by wire to Comrade Schevenels, on arriving here this afternoon we find that he and Comrade Jouhaux, as well as Stolz, had already left this morning for Moscow. We very much regret this unhappy coincidence, which, however, none of us could prevent, but we attach great importance to our informing responsible quarters of the Fédération Syndicale Internationale and supplying them with full information and data concerning the situation of the Federations within our Union General de Trabajadores. In view of this fact, and taking into account the great obstacles which under the present circumstances would make it extremely difficult for us to go to London, we beg you to make an effort and snatch a brief visit to Paris, so that we can meet you here. We sincerely hope that in spite of the much work weighing on you at present you will be able to grant our wish, and that early next week — let us say Monday or Tuesday - it will be possible for you to make this brief trip to Paris, for which we shall be extremely grateful to you. We should greatly esteem your early answer to our General Secretary, RODRIGUEZ VEGA, to this Hotel Moderne, Place de la République (Cable address: OTELDERNE PARIS), if possible by wire as the fact that we are at the weekend might delay a letter by airmail. Thanking you again very much in advance, and with very best wishes We remain Yours for the Cause For the Executive of the U.G.T., Felipe Pretel Treasurer Jose Rodriguez Vega, General Secretary. 292/946/11/18